Study of Munasabah on Words of Sakinah Mawaddah Rahmah and Its Stylistics - Khalim, Muhammad Nur; Taufiq, Mirwan Akhmad (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2023)
AbstractThe Holy Qur’an is a sacred book for Muslims. The reader can understand its meanings and secrets from different aspects, including munasabah and stylistics. This study aims to know the secrets of the appropriate choice of the words sakinah (serenity), mawaddah (affection),and rahmah (mercy) and their arrangement in verse among married couples who wanted a permanent marriage without regret according to the Qur’anic approach. This study relied on the descriptive analytical method of these three words that appeared in Surah Al-Rum, verse 21. The method of collecting its data was based on reviewing and repeated reading of that verse according to the opinions of mufassir who interpreted this verse. The study reached results that the interpreters differed in understanding the meanings of these three words, especially the meaning of sakinah between the meaning of reassurance, tranquillity, and well-being at the economic level. However, they agreed that sakinah is the primary goal in the marital relationship, and affection and compassion are two means of achieving the success of the marital relationship. The spatial arrangement of these words is highly eloquent in terms of munasabah and style.Keywords: Marital relationship; Munasabah; Quranic approach; Quranic stylistic. AbstrakAl-Qur'an adalah kitab suci bagi umat Islam, dimana pembaca dapat memahami makna dan rahasianya dari berbagai aspek, termasuk munasabah dan stilistika. Penelitian ini bertujuan untuk mengetahui rahasia pemilihan kata sakinah (ketenangan), mawaddah (kasih sayang), dan rahmah (rahmah) serta susunannya dalam ayat di kalangan pasangan suami istri yang menginginkan pernikahan tetap tanpa penyesalan dalam pandangan al-Qur'an. Penelitian ini menggunakan metode deskriptif analitis terhadap ketiga kata yang muncul dalam Surat Al-Rum ayat 21. Cara pengumpulan datanya berdasarkan penelaahan dan pembacaan ulang terhadap ayat tersebut sesuai dengan pendapat mufassir. Kajian ini menghasilkan bahwa para mufassir berbeda dalam memahami makna ketiga kata tersebut, khususnya makna sakinah antara makna ketentraman, dan kesejahteraan dalam tataran ekonomi. Namun mereka sepakat bahwa sakinah adalah tujuan utama dalam hubungan perkawinan, dan kasih sayang serta kasih sayang merupakan dua sarana untuk mencapai keberhasilan hubungan perkawinan. Penataan ruang kata-kata ini sangat fasih dalam hal munasabah dan gayanya.Kata Kunci: Hubungan Suami Isteri; Munasabah; Pendekatan Al-Qur’an; Stilistika Al-Qur’an.